Virtual refrigerator management system - Wong, Jiun Lin (2022)

(untitled)
Every since our country government had issued the Malaysia Movement Control Order (MCO), it could be found that lots of people would tend to stock up a lot of items or products in their home fridge. However, the above actions had caused some issues for the users to monitor the products within their fridge. A significant problem would be the difficulty of monitoring the item’s expiration date and position. It is a common issue when the fridge was filled with various types of items, user could hardly find the items that would need to use immediately if the target items were placed behind other products. Moreover, users would sometimes forget the exact expiration date for the items they had placed into the fridge especially for the fresh grocery products without proper expiration date labelled. Therefore, a virtual fridge system is necessary to be proposed in order to address the following issues. The final deliverable of this project is to provide a virtual mobile application platform that could assist users in monitoring the products in their fridge including the item’s expiration date and positioning issue. By using the features provided within this system, users could record every single item they had purchased such as the item’s name, category, type, expiration date and position. By this, the user could visually check every single item condition they had placed into their fridge via their mobiles. Further reminder and push notification features would also be integrated in current system such that the system could notify the users when special cases had occurred. Basic functionalities such as user registration, login, logout and authentication would also be implemented in this system to maintain the user confidentiality. This application is developed by using Android Studio as an IDE and Java as major programming language. The back-end database is supported by Google Firebase which is a cloud database that could ease the data monitoring process.